ARTISIPASI MASYARAKAT DALAM PENANGGULANGAN STUNTING DI DESA SINGAJAYA KECAMATAN INDRAMAYU KABUPATEN INDRAMAYU - Siddid Putra Pratama; Teuku Afrizal (Journal of Management and Public Policy, 2026)
This study aims to analyze the stages and forms of community participation in stunting prevention in Singajaya Village, Indramayu District, Indramayu Regency, while identifying its driving and inhibiting factors. Using a qualitative-descriptive approach, the research draws on three primary sources: semi-structured interviews with 12 key informants; direct observation of Posyandu activities, stunting forums (rembuk stunting), and field activities of community health workers (kader); and secondary data from official stunting program documents, village reports, and community health center (Puskesmas) archives. The results indicate that community participation unfolds across four stages according to the Cohen & Uphoff framework. In the decision-making stage, participation is limited to representative mechanisms. The implementation stage shows active involvement through Posyandu attendance and basic technical support, with kader acting as the spearhead. The benefit-sharing stage reflects consumptive participation, where residents utilize health services without management involvement. The evaluation stage remains top-down, dominated by health professionals with only informal community feedback. The study concludes that community participation is not yet fully inclusive, remaining largely passive and representative. The main recommendation is that the Singajaya Village Government must optimize community participation through deliberative planning at the neighborhood (RW) level, mobilizing paternal roles in community work, strengthening information via digital delegation cards, initiating local protein-based nutritional self-sufficiency, and establishing two way participatory evaluations.